(untitled) (Research, Society and Development, 2023)
The development of alternatives to conventional antibiotics against superbugs represents an important step to avoid the increasing resistance of bacteria observed in conventional treatments. Herein, it was evaluated the influence of different combinations of two active antibacterial components (chitosan and zinc oxide) and a host poly (vinyl alcohol - PVA) in membranes produced by the solvent casting technique. Those systems were evaluated in terms of the biofilm inactivation, kill-time assays and inhibition haloes against S. aureus (ATCC 25923) in membranes that must release reactive components while preserving their integrity and favoring the generation of reactive species to improve the antibacterial activity. The results suggest the potential of the combination of chitosan, zinc oxide and poly (vinyl alcohol) to inhibit the growth of S. aureus colonies since the PVA improved the dispersion of the components, whereas chitosan-ZnO chelate improves the mutual activity of the metal oxide and the natural polymer template.